2018
DOI: 10.3329/jbcbm.v3i1.36756
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric variation in the species of two subfamilies of lycaenid butterflies (Lepidoptera: Lycaenidae) of Bangladesh

Abstract: A laboratory examination was done on the morphometric variation of lycaenid butterflies. Identifying characteristics, viz. forewing length (FWL), hind wing length (HWL), body length (BdL) and antennal length (AntL) were used for the analysis. A total of 514 individuals of lycaenid butterflies was identified under two subfamilies Polyommatinae and Theclinae. Among them 265 individuals were placed under 19 species of Polyommatinae and 249 individuals under 25 species of Theclinae. ANOVA tests were conducted to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…In term of growth type, the LLRs between 13 equations of length indicated positive allometric (A+) growth for the common grass yellow butterfly, E. hecabe (L.) (Table 3). Due to lack of literature data on family Pieridae butterflies, it restrains to compare our results with other findings except the study by Mahdi et al [14] and Akand et al [15] on family Lycaenidae. Earlier, Akand et al [15] reported the lengths of the forewing, hindwing, body and antenna of 44 species of butterflies under the two subfamilies of the family Lycaenidae.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In term of growth type, the LLRs between 13 equations of length indicated positive allometric (A+) growth for the common grass yellow butterfly, E. hecabe (L.) (Table 3). Due to lack of literature data on family Pieridae butterflies, it restrains to compare our results with other findings except the study by Mahdi et al [14] and Akand et al [15] on family Lycaenidae. Earlier, Akand et al [15] reported the lengths of the forewing, hindwing, body and antenna of 44 species of butterflies under the two subfamilies of the family Lycaenidae.…”
Section: Resultsmentioning
confidence: 67%
“…Due to lack of literature data on family Pieridae butterflies, it restrains to compare our results with other findings except the study by Mahdi et al [14] and Akand et al [15] on family Lycaenidae. Earlier, Akand et al [15] reported the lengths of the forewing, hindwing, body and antenna of 44 species of butterflies under the two subfamilies of the family Lycaenidae. In this study, the mean of total length of the body was recorded as 16.10 ± 2.55 mm for E. hecabe, while the mean of the body length was recorded as average 9.942± 0.98 and 9.116 ± 0.42 mm for Chilades pandava and C. lajus respectively [14] .…”
Section: Resultsmentioning
confidence: 67%
“…C. pandava and Chilades lajus were described by morphometric aspects of these butterflies (Mahdi et al, 2018). An important tool of separation and identification of insects either species or groups was a morphometric variation and measurements (Daly, 1985;Digo et al, 2015;Akand et al, 2018). In addition, both shape and size of the insect body and wings was play important role to identify between the closely related taxa within and between insect species (Riva et al, 2001;Baylac et al, 2003;Tuzun, 2009).…”
Section: Monitoring Of Developmental Stages and Biological Aspectsmentioning
confidence: 99%
“…Pictures of the different stages were also taken using camera (64MP) to describe and determine by using of compu eye, leaf and symptom area program by Bakr (2005). A clear morphological scale measurement was used for the identifying variables according to Akand et al (2018). All the morphological characteristics (viz.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an understanding of flower use and flower preferences is required to manage habitats for butterflies (Hardy et al 2007). Some research on butterfly has been done for nectar plant choices in some forests and gardens of Bangladesh (Bashar et al 2006) including Bhawal and Madhupur Sal Forests (Akand et al 2017, Alam et al 2017, Kamrunnahar et al 2018. And study on species specific foraging behaviour stands as most essential attempt in the field of butterfly conservation research.…”
Section: Introductionmentioning
confidence: 99%